One false move - Haycock, Peter; Holt, Derek (<<The>> Criterion Collection, 2023)
"A small-town police chief (Bill Paxton) concealing an explosive secret. A pair of ruthless drug dealers (cowriter Billy Bob Thornton and Michael Beach) who leave a bloody trail in their wake as they make their way from Los Angeles to Arkansas. And an enigmatic woman (Cynda Williams) caught in the middle. The way these desperate lives converge becomes a masterclass in slow-burn tension thanks to the nuanced direction of Carl Franklin, whose haunting film travels a crooked road across America’s most fraught divisions—urban and rural, Black and white—while imbuing noir conventions with a wrenching emotional depth." [criterion.com]
Original: USA 1991
Director-approved Blu-ray special edition features: new 4K digital restoration, approved by director Carl Franklin, with 2.0 surround DTS-HD Master Audio soundtrack ; audio commentary from 1999 featuring Franklin ; new conversation between Franklin and cowriter-actor Billy Bob Thornton ; trailer ; English subtitles for the deaf and hard of hearing ; plus: An essay by author William Boyle
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc